Corneal Decompensation in Uveitis Patients: Incidence, Etiology, and Outcome. (19th May 2021) - Wong, Shiao W.; Carley, Fiona; Jones, Nicholas P.
ABSTRACT: Purpose : To identify the prevalence, etiology, management and visual outcomes of treatment in uveitis-related corneal decompensation. Patients and methods : This is a retrospective study of patients with corneal decompensation identified from a large cohort with uveitis in a tertiary referral clinic setting. Results : Between March 1991 and May 2018, 4132 new patients with uveitis were seen in Manchester Uveitis Clinic. Of these, 25 patients (0.6%) were identified with corneal decompensation of which 9 (0.2%) were affected bilaterally (total 34 eyes). The mean interval between uveitis diagnosis and decompensation was 23 months (range 0-117 m). Ten patients (41%) had associated glaucoma. Seventeen eyes (50%) had undergone intraocular surgery prior to decompensation. For eyes with no history of raised intraocular pressure or intraocular surgery, keratouveitis (presumed autoimmune or tuberculous) was the most common cause of corneal decompensation. Fourteen eyes (41%) required corneal graft and of these, five required repeat grafting. Conclusions : Corneal decompensation in eyes with uveitis is a rare but significant complication. Direct endothelial inflammation may alone cause decompensation, but in most eyes with uveitis, prior raised intraocular pressure or intraocular surgery are required to precipitate the cornea into decompensation. Outcomes of corneal transplantation in this group may be disappointing.